Potential Coastal Pollution from Agricultural Activities in Mexico - Azuz-Adeath, Isaac; Arreola-Sevilla, Roberto J.; Aguiar, Fernanda; Cabrera, Mireya (My University, 2022)
The pressures of agriculture on the pollution of coastal waters has increased worldwide due to the population demands of food, and the consequent increase in the use of agrochemical substances to maintain or improve productivity. This study estimates the potential pollution in coastal areas produced by the use of highly hazardous pesticides (HHP) in the agricultural activity of all coastal municipalities in Mexico. In 2017, a total of 21,6 million hectares of agricultural products were planted in Mexico, of which 13,3 million corresponded to coastal states (62 %) and 4,2 million to coastal municipalities (19 %). In all Mexican coastal states, at least in one municipality, HHP are applied to crops. In the reference year, 83 coastal municipalities covering a planted surface of 916 327 ha applied 280 tons of HHP. In addition to presenting the assessment of the quantity of agrochemicals used in Mexican coastal areas, some simple indicators were built considering the level of toxicity of the type of HHP used, the mean distance from the county to the sea, and the rain regime in each region -as a potential element of conduction of pollutants to the sea-. Using the proposed indicators, the highest level of potential coastal pollution occurs in the states of Sonora, Tamaulipas, Colima and Chiapas, where agricultural activities are potentially the most damaging to the coastal and marine environment. These simple calculations could help Mexican authorities to establish protective measures against the pollution of coastal areas through stronger regulations and integrated management programs.
Keywords: Agricultural activities; México; Campus Ensenada